2023
DOI: 10.1037/scp0000260
|View full text |Cite
|
Sign up to set email alerts
|

Depression and mysticism: Case report and literature review.

Abstract: The principal aim of this article is to explore the relationship between depression and mystical experiences. The paper begins with a discussion of definitional issues, inquiring into the meaning and interrelationship of terms such as peak experience, mystical experience, awakening experience, satori, and so forth. The case of a 68-yearold woman who underwent a profound and transformative experience while being treated for depression in the first author's psychiatric clinic is then presented as a basis for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
2
0
2
Order By: Relevance
“…A number of researchers have identified positive correlations of different NOEs with mental well-being or positive psychological states such as joy, enhanced sense of meaning or life purpose, and enhanced coping capacity in the face of suffering and bereavement (Benning et al, 2021;Bovero et al, 2019;Elsaesser et al, 2021;Jahn & Spencer-Thomas, 2018;Kalkstein & Tower, 2009;Kennedy et al, 1994;Kennedy & Kanthamani, 1995;Kent et al, 2020;Krause & Bastida, 2009;Lee, 2011;Rabeyron et al, 2018;Rudaz et al, 2019;Saiz et al, 2021;Wilde et al, 2019). In contrast, some investigations have found either inverse (Ballew et al, 2012;Ho et al, 2016;Koenig et al, 2016;Lee, 2011;Park & Roh, 2013;Simmonds-Moore et al, 2019;Whitaker et al, 2021) or no significant association between NOEs and psychopathological variables (Barnby & Bell, 2017;Caird, 1987;Cooper et al, 2015;Francis et al, 2015;Francis & Robbins, 2014;Kroll et al, 1996;Simmonds-Moore et al, 2019;Thalbourne, 2007).…”
Section: Relationships Between Noes and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers have identified positive correlations of different NOEs with mental well-being or positive psychological states such as joy, enhanced sense of meaning or life purpose, and enhanced coping capacity in the face of suffering and bereavement (Benning et al, 2021;Bovero et al, 2019;Elsaesser et al, 2021;Jahn & Spencer-Thomas, 2018;Kalkstein & Tower, 2009;Kennedy et al, 1994;Kennedy & Kanthamani, 1995;Kent et al, 2020;Krause & Bastida, 2009;Lee, 2011;Rabeyron et al, 2018;Rudaz et al, 2019;Saiz et al, 2021;Wilde et al, 2019). In contrast, some investigations have found either inverse (Ballew et al, 2012;Ho et al, 2016;Koenig et al, 2016;Lee, 2011;Park & Roh, 2013;Simmonds-Moore et al, 2019;Whitaker et al, 2021) or no significant association between NOEs and psychopathological variables (Barnby & Bell, 2017;Caird, 1987;Cooper et al, 2015;Francis et al, 2015;Francis & Robbins, 2014;Kroll et al, 1996;Simmonds-Moore et al, 2019;Thalbourne, 2007).…”
Section: Relationships Between Noes and Mental Healthmentioning
confidence: 99%
“…For example, it was found that a history of trauma and psychopathological symptoms is sometimes associated with NOEs such as dissociative and extrasensory perception experiences (Hecker et al, 2015;Rabeyron & Watt, 2010;Ross & Joshi, 1992;Scimeca et al, 2015 -but see Kroll et al, 1996). Other studies have found that NOEs such as NDEs and certain mystical experiences may trigger a transformational process that leads to posttraumatic growth and greater psychological integration (Benning et al, 2021;Khanna & Greyson, 2015;Royse & Badger, 2017).…”
Section: Relationships Between Noes and Mental Healthmentioning
confidence: 99%
“…Vários pesquisadores identificaram correlações positivas entre diferentes EREs e bem-estar subjetivo ou estados psicológicos positivos como alegria, maior senso de significado ou propósito de vida e maior capacidade de enfrentamento diante do sofrimento e do luto (KENNEDY, KANTHA-MANI, PALMER, 1994;KENNEDY, KANTHAMANI, 1995;ELLISON, FAN, 2008;KALKS-TEIN, TOWER, 2009;KRAUSE, BASTIDA, 2009;LEE, 2011;JAHN, SPENCER-THOMAS, 2018;RABEYRON et al, 2018;BOVERO et al, 2019;WILDE et al, 2019;KENT et al, 2020;BENNING, HARRIS;ROMINGER, 2021;ELSAESSER et al, 2021;SAIZ et al, 2021).…”
Section: Fatores Individuais E Psicossociais Na Relação Entre Eres E ...unclassified
“…É importante observar que os estudos considerados não permitem inferências muito seguras de causalidade, de modo que não sabemos se as experiências em questão são ocasionadas por processos traumáticos e psicopatológicos ou simplesmente moduladas de algum modo por estes; associação aqui não implica causa e efeito. De modo semelhante, mas em sentido oposto, outros estudos identificaram que EREs tais como as EQMs e certas vivências místicas de união com todo o universo ou um poder ou ser superior estão associadas a um processo transformacional positivo que leva ao crescimento pós-traumático e a uma maior integração psicológica (KHANNA, ROYSE, BADGER, 2017;BENNING, HARRIS, ROMINGER, 2021).…”
Section: Histórico De Psicopatologia E Traumaunclassified